Development of a Bacteriophage Cocktail to Constrain the Emergence of Phage-Resistant Pseudomonas aeruginosa - Yang, Yuhui; Shen, Wei; Zhong, Qiu; Chen, Qian; He, Xuesong; Baker, Jonathon L.; Xiong, Kun; Jin, Xiaoling; Wang, Jing; Hu, Fuquan; Le, Shuai (Frontiers in Microbiology, 2020)
With the emergence of multidrug-resistant and extensively drug-resistant bacterial pathogens, phage therapy and other alternative or additional therapeutic modalities are receiving resurgent attention. One of the major obstacles in developing effective phage therapies is the evolution of phage resistance in the bacterial host. When Pseudomonas aeruginosa was infected with a phage that uses O-antigen as receptor, phage resistances typically achieved through changing or loss of O-antigen structure. In this study, we showed that dsRNA phage phiYY uses core lipopolysaccharide as receptor and therefore efficiently kills the O-antigen deletion mutants. Furthermore, by phage training, we obtained PaoP5-m1, a derivative of dsDNA phage PaoP5, which is able to infect mutants with truncated O-antigen. We then generated a cocktail by mixing phiYY and PaoP5-m1 with additional three wide host range P. aeruginosa phages. The phage cocktail was effective against a diverse selection of clinical isolates of P. aeruginosa, and in the short-term constrained the appearance of the phage-resistant mutants that had beleaguered the effectiveness of single phage. Resistance to the 5-phage cocktail emerges after several days, and requires mutations in both wzy and migA Thus, this study provides an alternative strategy for designing phage cocktail and phage therapy.